2007
DOI: 10.1111/j.1365-2516.2007.01519.x
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal desmopressin (OctimTM): a safe and efficacious treatment option for children with bleeding disorders

Abstract: Desmopressin (1-deamino-8-D-arginine vasopressin (DDAVP)) has been shown to be an effective treatment option when administered both intravenously [1,2] and subcutaneously [3] to children with inherited bleeding disorders. We demonstrate here, both the efficacy and acceptability of a new intranasal DDAVP preparation, providing a cost effective treatment with good outcomes for children with bleed disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
0
10
0
3
Order By: Relevance
“…DDAVP (1-deamino-8-D-arginine vasopressin, desmopressin), a synthetic derivative of vasopressin that promotes the release of VWF multimers from Weibel-Palade bodies in the vascular endothelium, is safe and effective in preventing and treating bleeding in children with VWF levels < 50 iu/dl (Gilly, et al 2002, Khair, et al 2007, Leissinger, et al 2001). In our paediatric population, children are often tested for VWD due to a family history of VWD, personal bleeding history or prolonged partial thromboplastin time, as well as, but not limited to, part of a pre-operative evaluation.…”
mentioning
confidence: 99%
“…DDAVP (1-deamino-8-D-arginine vasopressin, desmopressin), a synthetic derivative of vasopressin that promotes the release of VWF multimers from Weibel-Palade bodies in the vascular endothelium, is safe and effective in preventing and treating bleeding in children with VWF levels < 50 iu/dl (Gilly, et al 2002, Khair, et al 2007, Leissinger, et al 2001). In our paediatric population, children are often tested for VWD due to a family history of VWD, personal bleeding history or prolonged partial thromboplastin time, as well as, but not limited to, part of a pre-operative evaluation.…”
mentioning
confidence: 99%
“…However, objective data on response of laboratory parameters were only obtained in a small subset of patients and no comparison to intravenous desmopressin was made. Khair et al also demonstrated that intranasal desmopressin appeared to be effective in a small group of paediatric patients with either haemophilia or von Willebrand disease but did not make a direct comparison to intravenous desmopressin. We did find one study which compared response to intranasal desmopressin with historic response to intravenous desmopressin within the same small group of paediatric patients .…”
Section: Discussionmentioning
confidence: 99%
“…Za dajanje v nos pri TT < 40 kg zadostuje en izbrizg (150 μg) DDAVP pripravka za nos (Octostim sprej®, 1,5 mg/ ml) v eno nosnico, pri TT > 40 kg pa enak odmerek v vsako nosnico (1,74,75).…”
Section: Dezmopresin -Ddavpunclassified